Updated S3 Guidelines – Diagnosis and Treatment of Colorectal Carcinoma: Relevance for Radiological Diagnosis and Intervention - Vogl, Thomas J.; Pereira, Philippe L.; Helmberger, Thomas; Schreyer, Andreas G.; Schmiegel, Wolff; Fischer, Sebastian; Herzog, Christopher (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2019)
The updated German S3 guidelines “Colorectal Carcinoma“ were created as part of the oncology program of the Association of the Scientific Medical Societies (AWMF), German Cancer Society and the German Cancer Aid under the auspices of the German Society for Digestive and Metabolic Disorders (DGVS) and they replace the previous guidelines from 2013. The main changes in the updated guidelines include the latest recommendations regarding endoscopy and adjuvant/neoadjuvant therapies as well as a complete restructuring of the section regarding therapeutic approach in metastases and in the palliative situation. The present manuscript discusses the importance of the current recommendations for radiological diagnosis and treatment and is intended to enhance the quality of patient information and patient care by widespread distribution.Key Points: Citation FormatDie aktualisierte deutsche S3-Leitlinie „Kolorektales Karzinom“ entstand im Rahmen des Leitlinienprogramms Onkologie der AWMF, Deutschen Krebsgesellschaft und Deutschen Krebshilfe unter Federführung der Deutschen Gesellschaft für Verdauungs- und Stoffwechselkrankheiten (DGVS) und ersetzt die bisherige Leitlinie aus dem Jahr 2013. Die wesentlichen Neuerungen der überarbeiteten Leitlinien umfassen neben aktualisierten Empfehlungen hinsichtlich Endoskopie und adjuvanter bzw. neoadjuvanter Therapien vor allem eine komplette Überarbeitung und Neustrukturierung des Abschnitts zum therapeutischen Vorgehen bei Metastasierung und in der palliativen Situation. Der vorliegende Artikel stellt die Bedeutung der aktuellen Verhaltensempfehlungen für die radiologische Diagnostik und Therapie dar und soll durch eine flächendeckendere Verbreitung der Qualitätssteigerung bei Patienteninformation und -versorgung dienen.Kernaussagen: Zitierweise
Keywords: colorectal cancer; ablation procedures; staging; S3 guidelines; follow-up